A dense gas dispersion model based on revised meteorological parameters and its performance evaluation. (1st January 2021) - He, Juanxia; Liu, Lei; Li, Angang; Ma, Ye; Zhou, Dongmei; Zhou, Qiyong; Zhan, Yongzhong
Abstract: Heavy gas dispersion is significantly impacted by meteorological conditions. In this study, the widely-used heavy gas dispersion model SLAB is revised by using alternative parametrizations for the meteorological parameters, mixing layer height, and wind speed profile. The Nozaki method and the stability modified logarithmic wind profile evolved from the Monin-Obukhov similarity theory are adopted to calculate the mixing layer height and wind speed profile in the improved SLAB-M model, respectively. Dense gas dispersion model evaluation protocols are used to evaluate SLAB-M, and the datasets from the Jack Rabbit II (JR II) 2015 Trials are used to compare the accuracy of the simulations to observed data. The statistical performance measures (SPMs) of SLAB-M are overall a little better than that of SLAB, and SLAB-M effectively simulates heavy gas dispersion under the different meteorological conditions of the JR II 2015 Trials. Thus, it can better satisfy the requirements of consequence assessment and emergency response for the leakage and dispersion of hazardous gasses. Graphical abstract: Image 1 Highlights: The algorithms of meteorological parameters in SLAB, i.e. mixing layer height and wind profile, were revised. An improved dense gas dispersion model named SLAB-M was obtained. The Jack Rabbit II 2015 Trials were simulated by SLAB and SLAB-M. The performance of SLAB-M was evaluated quantitatively, which shows improved agreement with the JRII 2015 maximum arc-wise concentrations.